Effect of Exports and Development Expenditures on Economic Growth Indonesia - Jumiana Jumiana (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
Economic growth is a significant increase in national income in a certain calculation period. This thesis is entitled